ATTITUDES TOWARDS THE ONLINE EDUCATIONAL ACTIVITY IN ROMANIAN PRE-UNIVERSITY EDUCATION WITHIN THE PANDEMIC CONTEXT - Sabina-Adina LUCA; Bogdan GHEORGHIŢĂ (Revista de Pedagogie, 2022)
Educational policy is, in a broad sense, the process of driving change and/or introducing innovations into the education system (Haddad & Demsky, 1995; Haheu-Munteanu, 2019). In the work of government, the ministries in charge usually aim to manage this process, starting from the assumed political programs. These imply strategic objectives, action directions or implementation strategies. Sometimes, however, the various crises affecting social systems, and therefore also the education system, require the implementation of contextual solutions, decisions taken under conditions of uncertainty. Given the context of the Covid-19 pandemic and the need to implement measures that meet the need to protect the health of students and teachers, we aim, through this study, to capture the range of attitudes and perceptions related to the policies implemented, as well as the various changes in the professional training of teachers, training “forced” by the need to use technology in online teaching. By means of a sociological survey based on an online questionnaire to Romanian pre-university teachers, we aim to inventory teachers’ reports on some aspects related to the pandemic context: the beginning of the pandemic and the frustration associated with this moment, the pandemic and the development of different digital skills, but also future projections about the desirability of using different tools and digital skills developed during the pandemic in “post-pandemic” teaching activity.